ACCase 6 is the essential acetyl-CoA carboxylase involved in fatty acid and mycolic acid biosynthesis in mycobacteria - Kurth, Daniel German (2009)
Mycolic acids are essential for the survival, virulence and antibiotic resistance of the human pathogen Mycobacterium tuberculosis. Inhibitors of mycolic acid biosynthesis, such as isoniazid and ethionamide, have been used as efficient drugs for the treatment of tuberculosis. However, the increase in cases of multidrug-resistant tuberculosis has prompted a search for new targets and agents that could also affect synthesis of mycolic acids. In mycobacteria, the acyl-CoA carboxylases (ACCases) provide the building blocks for de novo fatty acid biosynthesis by fatty acid synthase (FAS) I and for the elongation of FAS I products by the FAS II complex to produce meromycolic acids. By generating a conditional mutant in the accD6 gene of Mycobacterium smegmatis, we demonstrated that AccD6 is the essential carboxyltransferase component of the ACCase 6 enzyme complex implicated in the biosynthesis of malonyl-CoA, the substrate of the two FAS enzymes of Mycobacterium species. Based on the conserved structure of the AccD5 and AccD6 active sites we screened several inhibitors of AccD5 as potential inhibitors of AccD6 and found that the ligand NCI-172033 was capable of inhibiting AccD6 with an IC50 of 8 ìM. The compound showed bactericidal activity against several pathogenic Mycobacterium species by producing a strong inhibition of both fatty acid and mycolic acid biosynthesis at minimal inhibitory concentrations. Overexpression of accD6 in M. smegmatis conferred resistance to NCI-172033, confirming AccD6 as the main target of the inhibitor. These results define the biological role of a key ACCase in the biosynthesis of membrane and cell envelope fatty acids, and provide a new target, AccD6, for rational development of novel anti-mycobacterial drugs